Cyberfeminism Activities of Jakarta Feminist as an Effort to Create a Safe Space for the Society - Lasari, Yuni; Dewi, Sulih Indra (The Sunan Ampel Review of Political and Social Sciences, 2023)
Current technological developments support victims of violence in seeking an online environment that can facilitate a safe space from the threat of sexual and gender-based violence. Moreover, various social movements have emerged by individuals and organized groups that aim to carry out joint campaigns against this. Jakarta Feminist also does this on its social media. Utilizing various features on Instagram, the @Jakartafeminist account is taking steps towards cyberfeminism by creating various cyberspace programs, classes, and campaigns. This research uses a qualitative approach with a case study research method with data collection techniques are: observation, interviews, and documentation. The results of this research show that cyberfeminism carried out by Jakarta feminists originates from collaborative actions created offline and online by utilizing new media. All programs, classes, and campaigns are continuous with each other following the issues raised so that it is clear that Jakarta Feminist is trying to accommodate victims and survivors to have the safe space they need. Cyberfeminism is carried out using hashtags and content to build networks and carry out digital campaigns to increase community participation online.